Design and analysis of a novel wound rotor for a bearingless induction motor. Issue 12 (2nd December 2019) - Yang, Zebin; Ding, Qifeng; Sun, Xiaodong; Ji, Jialei; Zhao, Qian
ABSTRACT: The traditional squirrel-type bearingless induction motor (BIM) suspension winding generates induced current in its squirrel-cage rotor and affects the phase and amplitude of the suspension force. Based on the analysis of the spatial distribution of torque winding magnetic field and suspension winding magnetic field, a new type of wound rotor BIM is designed. Different from the squirrel-cage rotor, the wound rotor uses a special method of embedding a set of coils at any symmetrical four rotor slot positions, so as to only induce the torque winding magnetic field. The induced current, air-gap magnetic density, magnetic field line distribution, suspension force as well as electromagnetic torque of the traditional squirrel-cage motor and the new wound motor are analysed by Maxwell finite element calculation. The results show that the designed new wound BIM can not only effectively suppress the induced current of suspension winding, eliminating its influence on the suspension force, but also has a better starting performance.